Pre-screening and preventive quarantine likely explains the low SARS-CoV-2 prevalence among Norwegian conscripts - Arne J. Norheim; Einar K. Borud; Andreas Lind; Elin A. Fadum; Arne Taxt; Anneke Steens; Karoline Bragstad; Erling Rein; Espen Nakstad (Taylor & Francis Group, 2021)
Objective: We aim to discuss whether preventive quarantine can mitigate the spread of Covid-19 during the pandemic. Design: We did a cross-sectional, observational study design in a mass-screening program in the enrolment to the Norwegian military during April 19-28th 2020 (COVID-NOR-MIL). Subjects: 1170 presumptively healthy young Norwegian conscripts. Setting: A structured interview encouraged the coming conscripts to a self-imposed preventive quarantine the last two weeks before enrolment. Main outcome measures: All conscripts underwent a PCR-based test with nasopharyngeal swabs at the day of enrolment. Results: Only two tested positive. The study discusses the predictive value of the RT-PCR test and the risk of false positive and false negative results, particularly when using the test in a low-prevalent cohort, even if the test properties of sensitivity and specificity is almost 100%. Further, the study discusses the challenge of whether a positive SARS-CoV-2 PCR-test represent viable and contagious virus or only viral remnants. Conclusion: The adherence to self-imposed preventive quarantine is a challenge and is a subject to further research. Implications: We want to draw the attention to the potential value of a thorough pre-screening processes and self-imposed preventive quarantine to minimize the potential spread of SARS-Cov-2.